Proceedings of the Genetic and Evolutionary Computation Conference 2017
DOI: 10.1145/3071178.3080294
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up evolutionary multi-objective optimisation through diversity-based parent selection

Abstract: Parent selection in evolutionary algorithms for multi-objective optimization is usually performed by dominance mechanisms or indicator functions that prefer non-dominated points, while the reproduction phase involves the application of diversity mechanisms or other methods to achieve a good spread of the population along the Pareto front. We propose to re ne the parent selection on evolutionary multi-objective optimization with diversity-based metrics. e aim is to focus on individuals with a high diversity con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The results for OneMinMax also hold for Global SEMO (GSEMO) which uses standard bit mutations where every bit in the mutation step is flipped with probability 1/n. This article extends its conference version [6] in various ways. In [6] for LOTZ only SEMO was analysed as the analysis of GSEMO was too challenging.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results for OneMinMax also hold for Global SEMO (GSEMO) which uses standard bit mutations where every bit in the mutation step is flipped with probability 1/n. This article extends its conference version [6] in various ways. In [6] for LOTZ only SEMO was analysed as the analysis of GSEMO was too challenging.…”
Section: Introductionmentioning
confidence: 91%
“…This article extends its conference version [6] in various ways. In [6] for LOTZ only SEMO was analysed as the analysis of GSEMO was too challenging. Here we address this challenge by providing investigations for a variant of GSEMO on LOTZ.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…All results surveyed so far use diversity mechanisms in the environmental selection, i. e. to decide which search points are allowed to survive to the next generation. Here we present recent work by Covantes Osuna et al [5], who suggested to use diversity mechanisms in the parent selection in the context of evolutionary multiobjective optimization.…”
Section: Diversity-based Parent Selectionmentioning
confidence: 99%
“…Problems with similar features are found in combinatorial optimisation, for instances as worst-case examples for finding shortest paths [50]. Multiobjective variants like LOTZ are popular example functions in the theory of evolutionary multiobjective optimisation [7,21,28,34,41].…”
Section: Introductionmentioning
confidence: 99%